Source of gold in Neoarchean orogenic-type deposits in the North Atlantic Craton, Greenland: Insights for a proto-source of gold in sub-seafloor - Saintilan, N.J.; Selby, D.; Hughes, J.W.; Schlatter, D.M.; Kolb, J.; Boyce, A. (Karlsruhe, 2020)
Given that gold (Au) mostly remained in the incipient Earth mantle until ca. 3.9–3.8 Ga, a “proto-source” of gold may have been present in the dominantly mafic crust precursor born through first-stage melting of the early Earth mantle. In south-westernmost Greenland, a fragment of the North Atlantic Craton is characterised by greenstone belts comprising mafic volcanic and magmatic rocks, and harzburgite cumulates that were emplaced at ca.<3.19–3.01 Ga (e.g., Tartoq greenstone belt). Here, combining detailed sulphide petrography with rhenium- osmium-sulphur (Re-Os-S) isotope geochemistry of individual mineral separates of arsenopyrite from goldsulphide mineralised shear zones, we pinpoint the precipitation of ca. 3.18–3.13 Ga (Re-Os model ages) hydrothermal arsenopyrite associated and coeval with arc-related magmatism of the Tartoq Group. We consider sub-seafloor hydrothermal alteration of the oceanic crust and magmatic activity to have supplied arsenic (As), Re, and Au, to result in the precipitation of the ca. 3.18–3.13 Ga arsenopyrite with primary invisible gold. Additionally, in major shear zones in a rigid juvenile continental crust, retrograde greenschist-facies metamorphism overprinted the ca.>3.0 Ga prograde amphibolite-facies metamorphic assemblages and caused local dissolution of arsenopyrite. During this retrograde tectono-metamorphic stage, in gold-rich shear zones, the Re- Os geochronometer in arsenopyrite was reset to a Neoarchean age while invisible gold was liberated and deposited as free gold with 2.66 Ga pyrite (Re-Os isochron ages). The initial Os isotope ratios of Neoarchean arsenopyrite ($^{187}$Os/$^{188}$Os$_{i}$ = 0.13 ± 0.02) and gold-bearing pyrite (0.12 ± 0.02) overlap with the estimated ($^{187}$Os/$^{188}$Os ratio of the Mesoarchean mantle (0.11 ± 0.01) and preclude contribution of radiogenic crustal Os from evolved lithologies in the accretionary arc complex, but instead, favour a local contribution in Os from basaltic rocks and serpentinised harzburgite protoliths by metamorphic fluids. Thus, the ca. 2.66 Ga lode gold mineralisation identified in the North Atlantic Craton may illustrate a gold endowment in shear zones in Earth’s stabilizing continental crust at the time of the 2.75–2.55 Ga Global Gold Event, through metamorphic upgrading of bulk gold which had originally been extracted from the Mesoarchean mantle and concentrated in hydrothermal arsenopyrite deposits in oceanic crust beneath the overall reduced Mesoarchean ocean.